On Reverse – Centralizers Of Semiprime Rings - Hassan, Ali; Fadhil, Fatin (Iraqi Journal of Science, 2024)
In this paper we study necessary and sufficient conditions for a reverse- centralizer of a semiprime ring R to be orthogonal. We also prove that a reverse- centralizer T of a semiprime ring R having a commuting generalized inverse is orthogonal